A case of treatable encephalopathy, developmental regression, and proximal tremor. (December 2021) - Hull, Mariam; Emrick, Lisa; Sadat, Roa; Parnes, Mered
Abstract: Tyrosine hydroxylase (TH) deficiency is an autosomal recessive condition first described as a progressive, early-onset hypokinetic-rigid and dystonic syndrome that was responsive to levodopa. Here we present a child with developmental regression, proximal tremor, and encephalopathy found to have tyrosine hydroxylase deficiency in whom treatment resulted in acquisition of developmental milestones.